Animal models in cancer drug discovery - Azmi, Asfar S.; Mohammad, Ramzi M. (Academic Press, 2019)
Animal Models in Cancer Drug Discovery brings forward the most cutting-edge developments in tumor model systems for translational cancer research. The reader can find under this one volume virtually all types of existing and emerging tumor models in use by the research community. This book provides a deeper insight on how these newer models could de-risk modern drug discovery. Areas covered include up to date information on latest organoid derived models and newer genetic models. Additionally, the book discusses humanized animal tumor models for cancer immunotherapy and how they leverage personalized therapies. The chapter on larger animal, canine models and their use in and their use in pre-investigational new drug (pre-IND) development makes the volume unique. Unlike before, the incorporation of several simplified protocols, breeding methodologies, handling and assessment procedures to study drug intervention makes this book a must read. Animal Models in Cancer Drug Discovery is a valuable resource for basic and translational cancer researchers, drug discovery researchers, contract research organizations, and knowledge seekers at all levels in the biomedical field.